2022
DOI: 10.1128/jvi.01903-21
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 122 Affects both the Initiation and the Maintenance of Hepatitis C Virus Infections

Abstract: A liver-specific microRNA, miR-122, anneals to the HCV genomic 5’ terminus and is essential for virus replication in cell culture. However, bicistronic HCV replicons and full length RNAs with specific mutations in the 5’ UTR can replicate, albeit to low levels, without miR-122. In this study, we have identified that HCV RNAs lacking the structural gene region or having EMCV IRES-regulated translation had reduced requirements for miR-122. In addition, we found that a smaller proportion of cells supported miR-12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…RLuc-GNN also bears and inactivating GNN mutation within the NS5B RNA polymerase active site (Jones et al, 2007). The pJ6/JFH-1 mono RLuc-NS2 (“ Δcore-p7”) and pJ6/JFH-1 E1-p7 del (“ΔE1-p7”) plasmids – truncated versions of the Renilla reporter virus with deletions of structural genes through p7 – were provided by Dr. Joyce Wilson (University of Saskatchewan, Saskatoon, SK, Canada) (Panigrahi et al, 2022). The pJ6/JFH Δcore (“ΔCore”) plasmid consists of a truncated version of the Renilla reporter virus with a deletion of the core-coding gene that retained the first 15 codons (necessary for a functional HCV IRES) and the final 14 codons (which orient the E1 protein in the ER) of the core-coding sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RLuc-GNN also bears and inactivating GNN mutation within the NS5B RNA polymerase active site (Jones et al, 2007). The pJ6/JFH-1 mono RLuc-NS2 (“ Δcore-p7”) and pJ6/JFH-1 E1-p7 del (“ΔE1-p7”) plasmids – truncated versions of the Renilla reporter virus with deletions of structural genes through p7 – were provided by Dr. Joyce Wilson (University of Saskatchewan, Saskatoon, SK, Canada) (Panigrahi et al, 2022). The pJ6/JFH Δcore (“ΔCore”) plasmid consists of a truncated version of the Renilla reporter virus with a deletion of the core-coding gene that retained the first 15 codons (necessary for a functional HCV IRES) and the final 14 codons (which orient the E1 protein in the ER) of the core-coding sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Specific mutations in the 5’ UTR can circumvent some of these roles, by enabling the spontaneous formation of the functional SLII structure and/or by increasing base-pairing at the 5’ terminus to protect the viral genome from exoribonuclease-mediated decay, even in the absence of miR-122 (Chahal et al, 2021). In addition to these roles, miR-122 has been proposed to modulate viral RNA replication by facilitating the formation of replication organelles, potentially by facilitating the switch from translation to viral RNA replication, although the mechanism by which this occurs has not yet been fully elucidated (Panigrahi et al, 2022; Ono et al, 2017; Masaki et al, 2015; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miravirsen has completed Phase II clinical trials for the treatment of Hepatitis (Hep) C [ 58 ]. Miravirsen is a miR-122 inhibitor that sequesters miR-122, which has been implicated in the promotion of the Hep C virus (HCV) life cycle [ 140 ]. Clinical trials to date have shown a significant reduction of HCV viral load in patients treated with miravirsen [ 58 ].…”
Section: Rna Therapeuticsmentioning
confidence: 99%
“…Advanced reports have established that miRNAs have a pivotal role in HCV infection and pathogenesis. Many cellular miRNAs suppress the HCV RNA replicative cycle, while others enhance it [ 60 , 61 ].…”
Section: Micrornas In Liver Diseasesmentioning
confidence: 99%